MOBILE APPLICATION DEVELOPMENT FOR INVENTORY MANAGEMENT USING BARCODE TECHNOLOGY - Revy Ravly Sabbathino Sahetapy; Suhirman Suhirman (Jurnal Informatika Teknologi dan Sains (Jinteks), 2025)
Efficient inventory management plays a crucial role in ensuring accuracy, reducing operational delays, and supporting data-driven decision-making. This study develops a mobile inventory management application that integrates barcode scanning technology to enhance process efficiency. The research method includes requirement analysis, system design, development, and system evaluation. System testing involves black-box testing for functional validation, performance testing to measure response time, and usability evaluation using the System Usability Scale (SUS). Experimental results show that the application increases data entry speed by 43%, achieves barcode scanning accuracy up to 98.5%, and reduces human input errors by 72% compared to manual recording. Performance testing indicates an average response time of 1.2 seconds, meeting mobile application usability standards. These findings demonstrate that the proposed system significantly improves accuracy, speed, and reliability in inventory operations. The scientific contribution of this research is the formulation of a validated and replicable mobile–barcode integration model optimized for small and medium-scale businesses requiring real-time inventory control.